“El plan de desarrollo regional y su contribución económica región La Libertad” - Sichez Muñoz, Victor Alejandro (2019)
ABSTRACT The purpose of the present research is to determine how the Regional Development Plan contributes to the Economic Development in the La Libertad Region, as well as to prepare a proposal for a regional development plan that will generate greater economic development in the region. An investigation was carried out where the priorities of the provinces of the Freedom in economic matter were determined. The fundamental objective is therefore to determine how the Regional Development Plan contributes or contributes to the Region's Economic Development.The sample consisted of the twelve provinces representing the economic sectors of Liberty.. The aspects guiding the proposal were the theoretical foundations of the development economy and the country's production and based on the results obtained, it was found that the use of the competitive advantages of the region, expressed in the optimization of the agricultural sector, Mining, and industrial sectors. It is concluded that the provinces with the highest production and development are located in coastal areas such as Trujillo, Pacasmayo and Virú, and in the highlands, all those linked to agriculture and mining.